Family History and Smartphone Use Associated With Refractive Error in School-Aged Children - Rochmayani, Dewi Sari; Cahyaningsih, Oktaviani (Jurnal Kesehatan Masyarakat, 2024)
The prevalence of Refractive Error (RE) in school children tends to increase. The study aims to analyze the prevalence and determinants of RE in elementary school children. The research was carried out in 2022, using a cross-sectional design. The research population is 110 students in grades V and VI of Krapyak State Elementary School, Semarang City. A total of 80 students were selected as samples with purposive sampling techniques. Data collection was carried out by interview techniques using questionnaires. RE is measured by Snellen Chart examination and pinhole lens. The multiple logistic regression multivariate test was used for risk factor analysis. The bivariate analysis resulted in 6 variables eligible for inclusion in the multivariate analysis model. The results of the multivariate analysis showed that there were 2 risk factors for RE, namely: smartphone use ≥ 2 hours continuously per day (OR = 14.622 95% CI 1.124 - 190.181) and parental history (OR = 11.194, 95% CI 1.827 -65.567). The probability of RE if a student has both risk factors is 71%. The use of smartphones ≥ 2 hours continuously per day and the presence of parental history of RE are risk factors for RE events in elementary school students.